Differential Proteomic Analysis of Chinese Giant Salamander Liver in Response to Fasting - Geng, Xiaofang; Guo, Jianlin; Zhang, Lu; Sun, Jiyao; Zang, Xiayan; Qiao, Zhigang; Xu, Cunshuan (Frontiers in Physiology, 2020)
Chinese giant salamander Andrias davidianus has strong tolerance to starvation. Fasting triggers a complex array of adaptive metabolic responses, a process in which the liver plays a central role. Here, a high-throughput proteomic analysis was carried out on liver samples obtained from adult A. davidianus after 3, 7 and 11 months of fasting. As a result, the expression levels of 364 proteins were significantly changed in the fasted liver. Functional analysis demonstrated that the expression levels of key proteins involved in fatty acid oxidation, tricarboxylic acid cycle, gluconeogenesis, ketogenesis, amino acid oxidation, urea cycle and antioxidant systems were increased in the fasted liver, especially at 7 and 11 months after fasting. In contrast, the expression levels of vital proteins involved in pentose phosphate pathway and protein synthesis were decreased after fasting. We also found that fasting not only activated fatty acid oxidation and ketogenesis-related transcription factors PPARA and PPARGC1A, but also activated gluconeogenesis-related transcription factors FOXO1, HNF4A and KLF15. This study confirms the central role of lipid and acetyl-CoA metabolism in A. davidianus liver in response to fasting at the protein level and provides insights into the molecular mechanisms underlying the metabolic response of A. davidianus liver to fasting.